Studies on iced storage of common murrel (Channa striatus) - Surendran, P.K.; Gopakumar, K., Perigreen, P.A., Joseph, J. (Fishery Technology, 2021)
The iced storage characteristics of common murrel (Channa striatus) have been studied. The non-protein nitrogen and alpha amino nitrogen in the muscle of the fish decreased during iced storage and the total volatile base nitrogen at the end of iced storage was not high even though the fish became unacceptable during the period. There was steep decrease in total bacterial count during initial storages of storage and then increased steadily on further storage. The fish remained in acceptable condition for 8 to 9 days in ice.